Agriculture, food security, and rural development - Asian Development Bank.; India. Department of Economic Affairs. Economic Division (New Delhi : Oxford University Press, 2010)
Contributed articles presented at the inception meeting of Economic Division in the Department of Economic Affairs, Ministry of Finance in collaboration with Asian Development Bank in New Delhi on 2-3 September 2003 on agricultural policy programmes in India supported by ADB furthered through various decentralized institutions all over India.
Keywords: Agriculture and state -- India -- Congresses; Agriculture -- Economic aspects -- India -- Congresses; Food security -- India -- Congresses; Rural development -- India -- Congresses